PREVENTIVE EFFECTS OF FIGS POWDER & GARLIC POWDER IN MALE ALBINO RATS WITH INDUCED DYSLIPIDEMIA - CHANDIO , S; GHAFAR , B; ASIF , M; MANGI , NZ; ZAREEN , R; MANGI , FH; MEMON , SA (Biological and Clinical Sciences Research Journal, 2023)
Dyslipidemia is one of the predisposing factors for the development of cardiovascular diseases due to the formation of atherosclerosis. Statin drugs are commonly used for the management of dyslipidemia but due to different side effects, drug resistance and affordability issues now, researchers working on the different preventive and curative effects of different natural herbs, fruits, etc. this study aimed to evaluate & compare the preventive effects of Ficus Carica & Allium Sativum on serum lipid profile levels in albino rats on induction of dyslipidemia. This experimental study was conducted at the Department of Biochemistry Liaquat University of Medical & Health Sciences (LUMHS) Jamshoro, Pakistan. Total of 24 male albino rats weighing of 170-190 grams were purchased from the Ojha campus of DUMHS Karachi Pakistan and caged at the Animal House of Agriculture University Tando Jam Pakistan. Twenty-four male albino rats were divided into four groups; each group contained 6 rats, group A as control group received a normal diet; group B rats received high fatty diet; group C rats received high fatty diet along with figs powder; group D rats received a high fatty diet with garlic powder with the calculated and proper dose for six weeks. After six weeks, orbital capillary blood samples were drawn to estimate lipid profile parameters. Lipid profile performed on Cobas chemical analyzer of Roche Hitachi at Diagnostic & Research Laboratory LUMHS. The Statistical data was analyzed by SPSS version 21 by applying ANOVA test for significance. The serum cholesterol level was highly observed in group B rats, and serum cholesterol level was significantly (P < .001) low in the group C & D rats in comparison to group B male albino rats. The serum T.G. level is highly observed in group B rats, T.G.’s level is significantly (P < .001) low in the group C & D rats compared to group B male albino rats. The serum LDL level is highly observed in group B rats, with a significant serum LDL level (P = 0.05) low in the group C & D rats compared to group B male albino rats. The serum HDL level more decline in group B rats serum HDL level was significantly (P = 0.05) high in the group C & D rats with the comparison to group B male albino rats. Figs and garlic powder had a significant role in normal levels of different lipid profile parameters. This study concluded that figs powder and garlic powder could perform a preventive role in the development of dyslipidemia.